The Effect of Different Stabilizers on the Characteristics of Gluten-Free Dried Noodle from Arrowroot and Mung bean Flour - Rosano Darmawan, Stefanus; Sarofa, Ulya (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Dry noodles are one of the foods made from wheat flour. The availability of wheat in Indonesia does not match consumer demand, necessitating the use of alternative ingredients such as arrowroot flour and mung bean flour. The use of stabilizers like CMC, STPP, and Xanthan Gum is needed to improve the characteristics of dry noodles. This research aims to determine the effect of the proportion of arrowroot flour and mung bean flour with different types of stabilizers on the physicochemical and organoleptic characteristics of dry noodles. The experimental design used was a factorial CRD with two factors. Factor I was the proportion of arrowroot flour and mung bean flour and Factor II was the addition of different types of stabilizers. Data were analyzed using 5% ANOVA and 5% DMRT. There was a significant interaction (p?0.05) on the moisture content, ash, protein, fat, starch, rehydration capacity, cooking loss, elasticity, and organoleptic characteristics of aroma, texture, and overall appearance. There were no significant differences in the organoleptic characteristics of color and taste. The best treatment was the proportion of arrowroot flour and mung bean flour (60:40) with the addition of CMC stabilizer, which resulted in dry noodles with the following characteristics: moisture 11.392%, ash 1.919%, protein 11.592%, fat 1.378%, starch 54.720%, rehydration capacity 110.266%, cooking loss 6.398%, elasticity 0.314 N, aroma 4.200, color 4.040, taste 3.800, texture 4.200, and overall appearance 4.160.